ACHIEVEMENTS AND CHALLENGES OF EDUCATORS WORKING IN SEXUAL EDUCATION: SUBSIDIES FOR TEACHER TRAINING - Neide Damico Figueiró, Mary (2019)
Initial and continuing teacher education is urgent and necessary to work on sex education in schools, especially in a period of strong conservatism. Based on university research and extension projects carried out from 1995 to 2013 on continuing education in the area of Sex Education at the State University of Londrina (UEL-PR), this text intends to reflect on achievements, overcoming and challenges linked to the work of the educator and provide elements that support the performance of the professional trainers. Among some important achievements for the sex education educator, we can mention, for example, the broadening in his/her personal view about sexuality, a broadening that can reflect positively on his/her own sex life and the achievement of greater closeness and friendship with his/her students. The challenges are many and have been accentuated due to the strong wave of conservatism. One is the need to overcome shame and fear of talking about sex. We conclude that trainers and educators need to know the challenges and alternatives that give legal support to the teaching of sexuality in schools, so as not to be paralyzed by repressive actions made by the enemies of sex education. They also need to develop the strengthening and unity of professionals working in schools, starting with the knowledge of the meaning of planned and intentional sex education in the lives of children, adolescents and young people.